In vitro Antioxidant and Free Radical Scavenging Activity of Lippia alba (Verbenaceae) - Ali, Md Omar; Khatune, Naznin Ara; Parvin, Mst Shahnaj; Alam , A H M Khurshid; Rahman, Md Aziz Abdur (Bangladesh Pharmaceutical Journal, 2023)
The research was designated to investigate the polyphenolic contents and antioxidant activity of the aqueous ethanolic extract and various fractions from the plant Lippia alba (Mill.) (Family: Verbenaceae). The dried course powder was extracted with 5% aqueous ethanol to get ethanolic extract (LAE) that was partitioned successively with n-hexane (LAH), chloroform (LAC), ethyl acetate (LAA), and water (LAQ). All the extracts were tested for polyphenol contents and antioxidant activity. The phenolic contents and the flavonoid contents of LAE, LAH, LAC, LAA, and LAQ were found to be 97.463±0.36, 55.030±0.690, 91.343±0.120, 117.340±1.349 and 81.630±0.550 and 418.470±4.962, 583.847±2.274, 168.623±1.186, 161.970±1.793 and 392.257±4.856 mg of GAE/g of dried extractives, respectively. The data showed that LAA contained highest phenolics and LAH contains highest flavonoids content than that of other fractions. The flavonol contents and the proanthocyanidin contents of LAE, LAH, LAC, LAA, LAQ and standard (at 100 μg/ml each) were 0.611±0.01, 0.144±0.031, 1.938±0.023, 1.944±0.049, 0.385±0.007 and 0.984±0.025 and 0.087±0.005, 0.155±0.004, 0.068±0.002, 0.049±0.002, 0.056±0.003 and 1.533±0.044, respectively, indicating remarkable flavonoid contents of LAC and LAA when compare to standard. However, proanthocyanidin contents of the extractives are less than standard catechin. In total antioxidant activity and reducing power capacity assay LAE, LAH, LAC, LAA, LAQ and standard showed absorbance at 0.667±0.005, 0.753±0.046, 0.444±0.009, 0.409±0.005, 0.235±0.007 and 1.534±0.38 and 1.633±0.055, 0.258±0.033, 3.839±0.051, 2.301±0.004, 0.360±0.042, and 1.046±0.053, respectively. The results demonstrated that all the extractives of L. alba had appreciable antioxidant activity when compared to standard. In DPPH radical scavenging assay and hydroxyl radical scavenging assay, the IC50 of LAE, LAH, LAC, LAA, LAQ and standard were found to be 15.73±0.51, 58.90±1.86, 15.93±1.24, 3.84±0.18, 7.17±0.36 and 3.48±0.17 μg/ml and 10.95±0.560, 13.25±0.56, 11.69±0.69, 5.68±0.408, 6.36±0.581 and 6.50±0.271 μg/ml, respectively. The significant scavenging activity was found in LAA that was similar to standard BHT and catechin. All these observations demonstrated that the plant L. alba specially chloroform and ethyl acetate fractions might be a good source for antioxidative lead. Bangladesh Pharmaceutical Journal 26(1): 7-14, 2023 (January)